Determinants Analysis of Increasing Incidents of Stunting among Toddlers Aged 6-59 Months - Dewi Ariskawati; Prihayati; Ismarina (KHD-Production, 2024)
Stunting is a condition of failure to thrive in children under five (under five years) resulting from chronic malnutrition so that the child is too short for his age. High numbers stunting in Banten Province associated with many factors, including socioeconomic status, food intake, infections, maternal nutritional status, infectious diseases, micronutrient deficiencies and the environment. Suffering child stunting will be more susceptible to disease and as adults are at risk of developing degenerative diseases. This research aims to find out analysis determinants of the increase in the incidence of stunting in children aged 6-59 months in the working area of ​​the Cibeber Community Health Center, Cilegon City in 2024. This type of research is quantitative with a cross-sectional design. Independent variables are income, history of exclusive breastfeeding, immunization history, history of pregnancy checks, knowledge and attitudes. Meanwhile the dependent variable is stunting in toddlers aged 6-59 months. The population of all mothers who have stunted toddlers in the working area of ​​the Cibeber Health Center, Cilegon City in 2024. The total sample of 61 people was selected by simple random sampling—statistical test using test Chi square with 95% CI and logistic regression test. The results of statistical tests show that the variables history of exclusive breastfeeding, history of immunizations, and history of pregnancy checks do not have a significant relationship with an increase in the incidence of stunting (p>0.05). In contrast, the variables income (p=0.000; OR=8.584), knowledge (p=0.000; OR=6.685) and attitude (p=0.001; OR=4.254) have a significant relationship with an increase in the incidence of stunting.